2018
DOI: 10.1080/13814788.2018.1444748
|View full text |Cite
|
Sign up to set email alerts
|

Previous antibiotic exposure and antibiotic resistance of commensal Staphylococcus aureus in Spanish primary care

Abstract: Introduction: Commensal flora of healthy people is becoming an important reservoir of resistant bacteria.Objectives: To evaluate the relationship of previous antibiotic-dispensed and resistance pattern of strains of Staphylococcus aureus in primary care patients.Methods: A cross-sectional study was carried out in seven primary care centres in Catalonia, Spain, from October 2010 to May 2011, as part of the APRES (The appropriateness of prescribing antibiotics in primary care in Europe concerning antibiotic resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The difference in the susceptibility pattern of the isolates to the various antibiotics is probably dependent on the source of the bacterial contaminant as organisms without prior exposure may show low level susceptibility compared to pathogens of human origin with prior exposure [29].…”
Section: Antibiotics Susceptibility Pattern Of the Bacterial Isolatesmentioning
confidence: 99%
“…The difference in the susceptibility pattern of the isolates to the various antibiotics is probably dependent on the source of the bacterial contaminant as organisms without prior exposure may show low level susceptibility compared to pathogens of human origin with prior exposure [29].…”
Section: Antibiotics Susceptibility Pattern Of the Bacterial Isolatesmentioning
confidence: 99%
“…Staphylococcus strains are commonly associated with nosocomial infections. Furthermore, Boada et al (2018) report that approximately 20% of human population, predominantly children, may carry S. aureus. Results obtained by Sapkota et al (2016) showed that Staphylococcus aureus was the most common bacterial contaminant on objects in many hospital wards in Nepal.…”
Section: Staphylococcus Concentration and Identificationmentioning
confidence: 99%
“…During therapy initiation, around a quarter of patients indeed reported adverse drug reactions, and one-fifth of the interviewed patients experienced practical problems. Another paper favoured by three editors was the paper on antibiotic resistance by Albert Boada and his colleagues from Spain [4]. They found that penicillin-resistant staphylococci were statistically significantly associated with the number of packages of penicillin dispensed previously.…”
Section: Top-5 Most Valued Articlesmentioning
confidence: 99%